The Role of Engineering Workshop Practices in Modern Manufacturing Technologies - Mohit Agarwal (Journal of Advanced Research in Mechanical Engineering and Technology, 2025)
Engineering workshop practices form the foundation of modern manufacturing technologies, ensuring precision, efficiency, and high-quality production. Traditional workshop techniques, including machining, welding, and casting, have evolved with the integration of computer-aided manufacturing (CAM), additive manufacturing, and automation. These advancements have significantly enhanced productivity, reduced material waste, and improved product customization. This review explores the significance of workshop practices in modern industries, examining advancements in materials, digital tools, and smart manufacturing techniques. The role of CNC machining, robotics, lean manufacturing, and Industry 4.0 in transforming workshop operations is critically analyzed, highlighting their contributions to process optimization, real-time monitoring, and automation. The integration of artificial intelligence (AI), the Internet of Things (IoT), and digital twin technology has further enabled predictive maintenance and remote diagnostics, ensuring higher operational reliability. Additionally, the article discusses the impact of these advancements on workforce skill development, emphasizing the need for training in mechatronics, data analytics, and digital fabrication. Future trends in engineering workshops, including hybrid manufacturing, sustainable practices, and the implementation of cyber-physical systems, are also explored. As manufacturing continues to evolve, engineering workshops must adapt to new technologies, ensuring a seamless transition toward smart and sustainable production systems.